The Effect of Omnibank’s SME Clinic on Business Management Capacity and Knowledge: The Case of the Accra Metropolis - Turkson, J.A. (University of Ghana, 2019)
The purpose of this research was to determine the extent to which OmniBank’s SME Clinic has had a positive effect on the business management capacity and knowledge of owners/managers of SMEs in Ghana, with focus on the Accra Metropolis. This was done primarily through: determining the strengths and weaknesses of OmniBank’s SME Clinic and investigating the effect of OmniBank’s SME Clinic on the business management capacity and knowledge of owners/managers of SMEs. Looking at the research methodology that was employed, for data collection purposes, questionnaires were administered to the owners and managers of 197 SMEs that participated in the SME clinic. Meanwhile, semi-structured interviews were conducted with the Managing Director, Corporate Affairs Manager, Head of Project and Performance, Team Lead, the junior staff of the Performance Department, and junior staff of the Corporate Affairs Department of OmniBank Ghana Limited. The study’s results indicated that the strengths of the SME Clinic were that: the personnel were very knowledgeable; presented both relevant and interesting information; used training methods that matched the participating companies’ requirements; it improved the knowledge and skills of the employees of participating companies, and it improved the productivity of participating companies. The weaknesses, on the other hand, were that it utilized too much theory; had a tendency to start too late; did not cover enough subjects; did not allocate enough time to its presentations, and did not go very deep into explanations. Furthermore, it was brought to light that the SME Clinic had improved the business management capacity of SMEs in the Accra Metropolis positively, but not significantly; and that it had both positively and significantly improved the business management knowledge of these same SMEs.
MSc. Development Finance
Keywords: Omnibank; Reinforcement; Experiential Learning; Social Learning; Accra Metropolis